Assessment of prosperity gospel among charismatic churches in Kenya - Kirimi, Moses M.; Kiboss, Joel (Editon Consortium Journal of Arts, Humanities and Social Studies, 2021)
The researcher sought to investigate the rise of prosperity gospel and its momentum in the midst of the learned society who can read the Bible and get its true meaning. The Equation Theory guided the study. The theory is anchored on the principle of reward and retribution, which states that the goodness of a person is confirmed by physical wellbeing and material prosperity while a sinful person is defined by the opposite. The study was carried out in Kawagware, Nairobi County that is habited by good number of people, becoming a soft target for the prosperity gospel. The study targeted congregants attending Christian charismatic churches in the area. Multi-stage sampling techniques comprising of cluster, purposive, convenient and simple random sampling procedures were used to select the churches and congregants. Data was gathered using drop and pick questionnaire for congregants. Data was analysed using SPSS (version 20) and results summarised using descriptive statistics comprising of frequencies, percentages presented using tables. Prosperity gospel was found to be appealing to congregants as it was considered to address their economic wellbeing, social wellbeing, spiritual wellbeing, guaranteeing them for holiness according, having the spiritual appeal as well as promissory prophesies. As a show of commitment, the congregants attend the churches unwaveringly, participate in the church services, and sacrifice their time, offerings, tithes, and gifts. The researcher recommends that different players, government, faith-based and private organisations should provide economic opportunities and create awareness to people living in poverty stricken areas like the Kawangware to enable them make informed decision and have economic independence.
free
Keywords: appeal; charismatic churches; persistence; rise of gospel of prosperity